VALIDITAS DAN RELIABILITAS ANGKET KEMATANGAN EMOSI - Dadi Ramdani; Ecep Supriatna; Wiwin Yuliani (IKIP Siliwangi, 2023)
Emotional maturity plays an important role in the development of a student's personality. This has a significant impact on student behavior, especially in terms of responses to external stressors and physiological changes that may be caused by students. Emotional maturity also acts as a skill that allows individuals to control their emotions and respond to them at the right time. The result is a measuring tool for emotional maturity in the form of a questionnaire about emotional maturity that has passed the validity and reliability test stages. Students of SMKN 1 Pacet became the subject of this research. The research was conducted on. Class X consists of 50 students. A score of 0.882 was obtained in the reliability test and was classified in the high category. Meanwhile, after the validity test, 41 valid statements out of 60 statements contained in the questionnaire, it can be concluded that the questionnaire can be used to measure students' emotional maturity.Keywords:Emotional Maturity, Validity, Reliability